Reporting degree of deacetylation values of chitosan: the influence of analytical methods - Khan, TanveerAhmad; Peh, KokKhiang; Ch'ng, Hung Seng (Canadian Society for Pharmaceutical Sciences, 2002)
PURPOSE: To investigate and compare the effect of three analytical methods, hydrogen bromide titrimetry (HBr titrimetry), infrared spectroscopy (IR spectroscopy), and first derivative UV-spectrophotometry (FDUV-spectrophotometry) in the determination of degree of deacetylation (DD) of chitosan. METHODS: Three different chitosan samples were selected for the DD quantification employing HBR titrimetry, IR spectroscopy with samples in the forms of KBr disc (at ratios of 1:2 and 1:3) and thin film (concentrations of 0.5 percent and 1 percent), and FDUV- spectrophotometry. RESULTS: The mean DD values of chitosan samples obtained by HBr titrimetry was significantly lower (p < 0.05) compared to IR spectroscopy using film (concentrations of 0.5 and 1 percent) as well as FDUV-spectrophotometry (purified and unpurified samples), but were significantly higher (p< 0.005) than those obtained using IR spectroscopy using KBr disk except for Chit-S2 computed using baseline (a), which were closely comparable (p > 0.05). In the IR spectroscopic method, the DD values differed when computed using different baseline. It can be observed that the values calculated using baseline (b) was generally higher than those calculated using baseline (a). On the other hand, chitosan samples prepared in the form of film might not be significantly affected by the different baseline as no consistent trend was observed. For FDUV-spectrophotometry, the DD values of purified Chit-S2 samples dried using oven and freeze dryer were comparable and not significantly different (p > 0.05). Similarly, no significant difference was observed for unpurified chitosan samples when dried using freeze dryer and oven (p > 0.05). Furthermore, the DD values of the purified and unpurified chitosan samples dried using freeze dryer were not significantly different except for Chit-S2. CONCLUSION: The DD values of chitosan were highly affected by the analytical methods employed. Hence, we proposed that the quantification method for DD should also be stated when reporting the DD value of chitosan sample.